Effectiveness of Emollient Topical Therapy on Hand Dermatitis Events - Pranesti, Rahma; Sutrisna, Em; Faradisa, Nida; Pramuningtyas, Ratih (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Background: Clinically, hand dermatitis manifests as either irritant contact dermatitis (ICD) or allergy contact dermatitis (ACD). Patients with hand dermatitis typically use emollients to reduce transepidermal water loss (TEWL).Objective: This investigation aims to evaluate the efficacy of emollient topical therapy on hand dermatitis.Methods: The study's design was based on a literature review, and the research samples were obtained through online searches on Google Scholar, PubMed, and ScienceDirect.Results: 495 items were subsequently excluded based on the restriction criteria. We obtained eight research articles for evaluation. Hand Eczema Severity Index (HECSI), TEWL, Dermatology Life Quality Index (DLQI), Health-related quality of life (HRQoL), Modified Total Lesion Symptom Score (mTLSS), Investigator Global Assessment (IGA), and Visual analog score (VAS) were used to measure hand dermatitis, and there was a significant increase in these measurements for emollients. In the conclusion of the eight articles, six stated that they were significant, and two stated that emollients were effectively used as topical therapy.Conclusion: Emollients typically act on the epidermis, particularly the stratum corneum, which can reduce TEWL so that antigen penetration and inflammation spread are not facilitated.